2021
DOI: 10.3390/diagnostics11030431
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Reliability of the Endoscopic Ultrasound Criteria for the Diagnosis of Early Chronic Pancreatitis: Comparison between the 2009 and 2019 Japanese Diagnostic Criteria

Abstract: In 2009, diagnostic criteria for early chronic pancreatitis (DCECP2009) were proposed by the Japan Pancreas Society. This study aimed to evaluate the interobserver reliability (IOR) of endoscopic ultrasound (EUS) criteria for diagnosis of early chronic pancreatitis (ECP) between DCECP2009 and 2019 diagnostic criteria for ECP (DCECP2019) to assess the validity of the revision from the perspective of EUS findings. Among patients who underwent a detailed observation of the pancreas by EUS at our institution betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…3 This revision resulted in a higher IOR than that obtained when using DC2009. 21 However, no further reports are yet available. Our study confirmed the validity of this criterion by demonstrating a high IOR for EUS findings (κ = 0.74 for hyperechoic foci/stranding; κ = 0.66 for lobularity) and the correlation between EUS findings and histological features.…”
Section: Endoscopic Ultrasonography and Histologymentioning
confidence: 99%
“…3 This revision resulted in a higher IOR than that obtained when using DC2009. 21 However, no further reports are yet available. Our study confirmed the validity of this criterion by demonstrating a high IOR for EUS findings (κ = 0.74 for hyperechoic foci/stranding; κ = 0.66 for lobularity) and the correlation between EUS findings and histological features.…”
Section: Endoscopic Ultrasonography and Histologymentioning
confidence: 99%
“…First, the trans-abdomen shear wave elastography is interfered by central obesity, exemplified by a case in the current study and who eventually underwent EUS to diagnose early chronic pancreatitis. Second, EUS is an invasive procedure with inter-observer variability, showing a kappa value (level of agreement) of about 0.6–0.8 [ 15 , 18 , 49 ]. The optimal resolution is probably the EUS technique combined with shear wave measurement, which objectively and quantitatively assesses the stiffness of pancreatic parenchyma [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the changes in EUS findings with DCECP2019 and examined the validity of the revision. 31 The overall concordance rate of EUS findings in the old criteria in 2009 (DCECP2009) was K ‐value = 0.424, and the overall diagnostic concordance rate of EUS findings in DCECP 2019 was K‐ value = 0.618. DCECP2019 combines EUS findings that were similar to DCECP2009.…”
Section: Comparison Of Eus Findings With Histopathological Findingsmentioning
confidence: 95%
“…Some reports have compared the diagnostic performance of conventional methods with that of the Rosemont classification, but no significant differences in the correct diagnosis rates are clear, partly because of interobserver reliability (IOR) and the complexity of the Rosemont classification. 24 , 25 , 26 , 27 , 30 , 31 …”
Section: Diagnosis Of Cp Using Eusmentioning
confidence: 99%